2009
DOI: 10.2471/blt.08.050740
|View full text |Cite
|
Sign up to set email alerts
|

Why first-level heatlh workers fail to follow guidelines for managing severe disease in children in the Coast Region, the United Republic of Tanzania

Abstract: Objective To determine why health workers fail to follow integrated management of childhood illness (IMCI) guidelines for severely ill children at first-level outpatient health facilities in rural areas of the United Republic of Tanzania. Methods Retrospective and prospective case reviews of severely ill children aged < 5 years were conducted at health facilities in four districts. We ascertained treatment and examined the characteristics associated with referral, conducted follow-up interviews with parents of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 32 publications
6
64
0
Order By: Relevance
“…One of these was the lack of country-specific data to inform our parameter for access to hospital care. We assumed that 61% of people who were referred to hospital would access hospital care, based on data from a retrospective case review study of children with severe pneumonia in Tanzania 24 . More realistically, we know that the proportion of children reaching an appropriate health facility may vary significantly between countries and so having one single parameter for all countries could result in inaccurate estimates.…”
Section: Discussionmentioning
confidence: 99%
“…One of these was the lack of country-specific data to inform our parameter for access to hospital care. We assumed that 61% of people who were referred to hospital would access hospital care, based on data from a retrospective case review study of children with severe pneumonia in Tanzania 24 . More realistically, we know that the proportion of children reaching an appropriate health facility may vary significantly between countries and so having one single parameter for all countries could result in inaccurate estimates.…”
Section: Discussionmentioning
confidence: 99%
“…One study in Tanzania found that only 25% of severely ill children seen at rural health facilities with IMCI-trained HCW's were referred [28]. Over 50% of HCW's indicated that they manage severe malaria and severe pneumonia in a rural health facility without referral, and that they are confident in their ability to manage severely ill children who do not have severe anemia, severe dehydration, or difficulty breathing.…”
Section: Inadequate Referral and Counselingmentioning
confidence: 94%
“…As a result, many HCW's prefer to follow the IMCI algorithms from memory, and compliance with algorithms appears to decrease several weeks following training [25,28]. While there are many potential interventions that could improve HCW compliance, current literature has not yielded many clear evidence-based solutions.…”
Section: Health Workforce and Information: Improving Training Supervmentioning
confidence: 99%
“…A study in Tanzania also showed poor adherence to IMCI guidelines for managing under-five children after IMCI training. 7 A community based study conducted in Rajasthan quoted that after IMCI training given to doctors in intervention area, 15% of intervention group mothers and 10% of control group mothers sought care from an appropriate provider promptly; one month after training, intervention site doctors counselled more effectively than control group doctors, but at six months their performance had declined 8. Our previous study also showed that the HSPs knowledge and skills was improved immediately after IMNCI training but it was declined over a period of time 9,10 . With respect to general dangers sign more than half of the mothers (55.4%) were explained about the 3-5 general dangers signs like lethargy or unconscious, inability to feed /drink, vomiting everything, convulsion by HSPs.…”
Section: Discussionmentioning
confidence: 99%